To yoga or not to yoga? The effect of yoga on sustained attention: an fNIRS Study - Cunningham, Cornelia (Rhodes University, Faculty of Humanities, Department of Psychology)
Deficits in sustained attention are ubiquitous across numerous neuropsychological disorders. Besides being critical in learning, memory, and general cognitive capacity, sustained attention is thought to be the primary foundation for 'higher' cognitive functions including, divided, selective, and focused attention. Despite the above, sustained attention remains the lesser-researched form of attention. Sustained attention is thought to be regulated by the default mode network and the central executive network, the latter of which is situated in the dorsolateral prefrontal cortex (DLPFC), a brain region typically associated with sustained attention. Given the contributions of sustained attention in overall cognitive functioning, alternative and natural methods used to enhance this type of executive function are important. One alternative method is yoga exercise, where yoga is thought to place the body into the most favourable state to enhance sustained attention capacity. This study found a significant (p = 0.018) difference between the yoga and control group in incongruent response accuracy scores in the SCWT. However, no statistically significant differences (p < 0.05) were observed in fNIRS individual and group analyses, SCWT congruent and incongruent reaction time, as well as congruent response accuracy. This suggests that short-term yoga practice may improve behavioural markers for sustained attention, at least in terms of cognitive interference.
Keywords: Yoga; Vigilance (Psychology); fNIRS; Neuroplasticity; Executive functions (Neuropsychology); Non-randomized controlled trial report